Escriptura exposada, registres escrits i oralitat en la pràctica administrativa medieval. L’organització dels treballs comunals a Vila-real i Castelló (segles XIV-XV). - Viciano, Pau (Scripta, 2022)
The exposed writing in the spaces of the city during the Middle Ages and the Early Modern Europe has been associated especially with the monumental or «apparatus» writing that celebrated power, as propaganda and memory. However, from the urban institutions were produced writings exposed, of mural character, with a purpose of practical communication, ephemeral, and, therefore, devoid of any vocation of monumentality. This type of public writing, although no material evidence is preserved, is documented in the administrative records of a Valencian small city such as Vila-real from the 14th-15th centuries. The textual references show that, at the request of the municipal authorities, inscriptions were made on the walls to organize a community service, such as military service. This is a practice that is embedded in organizational procedures based on written paper records but where oral communication continued to be prominent.